Von Willebrand factor (vWF) in plasma of patients with pancreatic carcinoma - Markocka-Mączka, Krystyna (Contemporary Oncology/Współczesna Onkologia, 2002)
In primary hemostasis vWF plays the key role in adhesion of platelets to damaged vascular endothelium and it results in later platelets aggregations. vWf seemed to be responsible only for inhibition of blooding until recently. Presently its role as a biochemical marker of endothelial damage is underlined. The aim of the study was to evaluate vWF concentration in plasma of patients with pancreatic carcinoma in its exocrine part. Examinations were carried out on healthy population (n=32, median age 54) and on patients with pancreatic cancer (n=32, median age 63.5). All patients with pancreatic carcinoma of its exocrine part had intraoperative histological verification. In majority of patients neoplasmas were in an advanced phase and presence of remote metastases was found in 18 patients. None of examined patients showed clinical manifestations of thrombosis. Blood samples for laboratory tests were drown 2-3 days before surgery. Patients did not undergo radio or chemiotherapy until blood was drown for laboratory tests. vWF was analysed with immunoenzymatic method (ELISA) according to producer's instructions. Levels of vWF concentration in examined samples were expressed in percentage of normal concentration in healthy adult subjects. Significance of differences in examined groups with abnormal pattern was checked with Kruskal-Wallis non-parametric test. Concentrations of vWF higher than the upper limits in healthy people were found in 37.5% of patients with pancreatic cancer. Lower concentrations than the bottom limits for control group were found in 6.3% patients. Results that did not match the limits defined by healthy control group concerned then 43.8% patients. Differences of median concentrations in compared groups were statistically significant (p<0.05). However, vWF concentrations in group of patients with remote metastases and without metastases did not show statistically significant difference. The results confirm observations of other authors demonstrating that abnormalities in blood coagulation in neoplasmatic patients do not depend on the advancement of cancer. Increased concentration of vWF in plasma of patients with pancreatic carcinoma is one of elements that may explain quite big tendency to thrombotic activity in these patients.